Implementasi Prosedur Dalam Produk Kredit Usaha Rakyat Pada PT Bank Dki Cabang Syariah Pondok Indah - Artika (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2023)
Artika. Internship Report of the Accounting Study Program, Tri Bhakti College of Economics entitled "Implementation of Procedures in Kredit Usaha Rakyat Products at PT Bank DKI Pondok Indah Syariah Branch". The purpose of making an internship report is to find out what the procedure is for the Kredit Usaha Rakyat (KUR) financing product and what are the requirements needed to apply for KUR financing at PT Bank DKI Pondok Indah sharia branch. This research was conducted at PT Bank DKI Pondok Indah sharia branch which is a company engaged in the banking business, the types of products offered are Savings, Financing, Treasury & Financial Institutions and Services. Data collection techniques used are documentation and literature study. The results of research conducted at PT Bank DKI Pondok Indah sharia branch show that the procedures for administering and document requirements for Kredit Usaha Rakyat (KUR) PT Bank DKI Pondok Indah sharia branch have been regulated in the SOP which the author describes through a flowchart involving several parties, namely Customers, Relationships Manager (RM), Head of Branch and Administration of Credit & Financing. The process starts from the customer applying for financing to filing documents. Bank DKI Pondok Indah sharia branch already has good procedures for financing Kredit Usaha Rakyat (KUR). Keywords: Procedures, Financing, Kredit Usaha Rakyat (KUR)